Purification of Mouse Interferon by Affinity Chromatography on a Solid-Phase Immunoadsorbent - Sipe, Jean D. (1973)
A solid-phase immunoadsorbent capable of binding mouse interferon has been prepared. Starting from crude tissue-culture material, interferon could be purified 1990 times in a single step of affinity chromatography. Overall recovery ranged from 55 to 103% with tissue culture and mouse-brain interferon; however, only 5% was obtained with Sendai virus-induced interferon from mouse serum.